Penegakan Hukum Terhadap Tindak Pelecehan Seksual Catcalling Dalam Perspektif Hukum Pidana Indonesia - Salsa Putri Diandra; Sofa Laela (PT. Hasba Edukasi Mandiri, 2025)
Verbal sexual harassment, including catcalling, is an act that often occurs but is considered trivial or even normalized in society. This study aims to examine the legal regulation of catcalling in Indonesian laws and regulations as well as to find out its law enforcement in the perspective of criminal law. Using a normative juridical approach, this research analyses relevant legal regulations, such as the Law on Sexual Violence (UU TPKS), the Criminal Code (KUHP), and other related regulations. The research findings show that catcalling is an act that violates human rights and norms of decency and has been regulated in various regulations in Indonesia, including the 1945 Constitution, the Criminal Code, the Pornography Law, and the TPKS Law. Although the term catcalling is not explicitly mentioned in these regulations, this act has fulfilled the elements of a criminal offense of decency, non-physical sexual harassment, and violation of individuals rights. Despite this regulation, law enforcement is still constrained by a number of factors, including the lack of public awareness of the seriousness of this act, cultural barriers, and limitations in the law enforcement system. In addition, conflict resolution through a restorative justice approach is often applied, which although providing a peaceful solution, is considered to have less of a deterrent effect on perpetrators.